The design model of unbound granular materials for flexible pavement - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (Engineers Media Pty Ltd, 2012)
This study aims to introduce an alternative design model of unbound granular base course materials by utilising laboratory test results such as resilient modulus, permanent deformation and bearing capacity of base course materials. Current pavement designs mostly overlook all problematical behaviours of unbound granular base layers and consider only as a layer transferring traffic loads to underneath layers regardless on the unbound granular base course deteriorations. Based on the existing design protocols in Australia, there are only the design criteria of the horizontal tensile strains at the bottom of the asphalt layer and the vertical deformations occurring at the top of the subgrade. The actual performances of granular base course materials under traffic loads have been rarely accounted into the pavement design protocol. Currently, road activities are growing in terms of magnitude and frequency far beyond the past and causing the early road damages leading to major road maintenances. The study presents hypothetically the more ratiotial approach of the stress and strain distribution in a flexible pavement using the finite element method with sophisticated laboratory results. In this study, the effects of a traffic load and material attributes which they were generated when vehicle travels, hence stress and strain contributing between tires and characteristics of unbound granular pavement materials were investigated. Moreover, the alternative design model for unbound granular layers was defined in order to draw up the guideline and recommendation on the current pavement analysis and design. © Institution of Engineers Australia, 2012.